O processo de consolidação da propriedade como centro do ordenamento jurídico moderno: uma leitura - Gamba, João Roberto Gorini (2014)
The present work is dedicated to the study of the property throughout a historical reconstruction of the institute according to the treatment given to it in legal, economic and social aspects, seeking to identify their philosophical foundations as well as the consequences verified by each adopted model. Initially, we looked for to expose conjectures about the origin of property in a primitive human stage and, in the following moment, pointing out the various transformations undergone by the institute since its apprehension by Roman Law until its receipt by the Napoleonic Code which, as the reading done, consolidates the property as the center of the modern legal system